Tourism analysis - "Smith, Stephen L.J." (Essex, 1989)
Sustainable tourism is a topic which is currently attracting enormous international attention. This book provides an up-to-date, comprehensive textbook on the practice and management of the subject. It offers a critical view of current thinking in the sustainable tourism field. Furthermore, it looks at sustainability in different sectors of tourism and in different parts of the world. A range of key issues and current debates are also discussed and numerous examples of sustainable tourism management practice from around the world are given. The book is designed to be interactive, with group and individual exercises and discussion points to further understanding of the subject. This book is essential reading for undergraduate students of tourism. It will also be of interest to students of urban and regional planning, leisure studies, environmental management and geography and also for practitioners involved in tourism policy and planning.
Keywords: Tourist trade